PERANCANGAN FASILITAS EDUPLAY TOYS BERBASIS BUDAYA LOKAL - Maria Yovita; Helena Robertha; Audrey Olivia (Serat Rupa: Journal of Design, 2020)
The train is one of the most widely used transportation options by people in Indonesia. Of course, this affects the quality of comfort in the waiting room at the station. Some of the factors causing the decreasing quality of comfort in waiting rooms at stations are reduced space circulation and increased noise pollution. One source of the causes of increased noise pollution are children. To minimize the noise pollution produced by children, we need a facility that can attract the attention of children. Therefore, the Eduplay Toys facility was designed. The method used in the design process of Eduplay Toys is the Design Thinking method which has five stages namely the Empathize, Define, Ideate, Prototype, and Test stages. The results of the application of Eduplay Toys besides being able to minimize the noise pollution produced by children can be used as a medium to provide learning about culture and tourism in Indonesia to children.